Unravelling the regulatory network controlling lateral root hydropatterning - Banda, Jason (2021)
The 3-dimensional shape of a root system is of crucial importance to its ability to take up nutrients and water. As these resources are heterogeneously distributed in the soil, plants need to adapt their root growth to aid foraging. One such adaptive response is termed lateral root (LR) hydropatterning where roots branch towards areas with higher water availability.